2015
DOI: 10.1007/s11356-015-5555-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and mobility of organic contaminants in soil: new three-step ecotoxicological evaluation

Abstract: A novel approach was developed for rapid assessment of bioavailability and potential mobility of contaminants in soil. The response of the same test organism to the organic extract, water extract and solid phase of soil was recorded and compared. This approach was designed to give an initial estimate of the total organic toxicity (response to organic extractable fraction), as well as the mobile (response to water extract) and bioavailable fraction (response to solid phase) of soil samples. Eighteen soil sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…This is mainly explained by the phenomena of biostimulation and bioaugmentation of soil microorganisms through the supply of nutrients and exogenous biodegraders brought along with sludge amendments (Ambrazaitiene et al., 2013; Hamdi et al., 2007b). Furthermore, it has been shown that the bioavailability of contaminants in soil decreases with increasing concentrations of organic C owing to the enhancement of soil adsorption capacity (Navarro, 2012; Prokop, Nečasová, Klánová, & Čupr, 2015). As for heavy metal immobilization, clay–humic complexes play very important roles in regulating the transport and retention of hydrophobic organic contaminants in soils (Wang & Xing, 2005)…”
Section: Resultsmentioning
confidence: 99%
“…This is mainly explained by the phenomena of biostimulation and bioaugmentation of soil microorganisms through the supply of nutrients and exogenous biodegraders brought along with sludge amendments (Ambrazaitiene et al., 2013; Hamdi et al., 2007b). Furthermore, it has been shown that the bioavailability of contaminants in soil decreases with increasing concentrations of organic C owing to the enhancement of soil adsorption capacity (Navarro, 2012; Prokop, Nečasová, Klánová, & Čupr, 2015). As for heavy metal immobilization, clay–humic complexes play very important roles in regulating the transport and retention of hydrophobic organic contaminants in soils (Wang & Xing, 2005)…”
Section: Resultsmentioning
confidence: 99%
“…The acute toxicity was determined by following the 81.9% basic test method for the liquid samples [10,11], and the Basic Solid-Phase Test with nine serial dilutions of the test solution for the soil samples [12]. With contaminated soil samples, the toxicity tests were carried out in three phases of water extract, solid-phase, and organic extract to assess the bioavailability and potential mobility of contaminants in soil [13]. The water extracts were used to test the mobile fraction of the contaminants, while the soil slurry were used to test the bioavailable fraction of the contaminants [13].…”
Section: Toxicity Tests Using Allivibrio Fischerimentioning
confidence: 99%
“…With contaminated soil samples, the toxicity tests were carried out in three phases of water extract, solid-phase, and organic extract to assess the bioavailability and potential mobility of contaminants in soil [13]. The water extracts were used to test the mobile fraction of the contaminants, while the soil slurry were used to test the bioavailable fraction of the contaminants [13]. The organic extracts are used to represent the total organic toxicity of the contaminated soil [13]; however, in this study, the toxicity obtained using the dioxin standards was used to represent the total organic toxicity of dioxins in contaminated soils.…”
Section: Toxicity Tests Using Allivibrio Fischerimentioning
confidence: 99%
See 2 more Smart Citations